Efficiency of auricular acupuncture in climacteric symptoms after cancer treatments. (3rd May 2016) - Viel, E.; Vanoli, A.; Melis, A.; Rocher, F.; Schipman, B.; Truong, D.
ABSTRACT: Objectives: This paper aims to highlight the efficiency of auriculotherapy in the treatment of hot flushes, especially in cancer-related menopausal transition. Methods: We used systematically collected data from patients in 2014 in a medical oncology practice. The treatment was made according to the guidelines of The Inter-University Diploma and the cartography of the World Health Organization; data on satisfaction were collected orally. Results: In 2014, 49 patients, among whom 41 had cancer, were treated for hot flushes. Although it is not recommended to treat several symptoms during the same session, we dealt with 1.7 symptoms per session on average. Sixty-nine percent of the patients were satisfied. We lacked data for nine patients, who did not come to the minimal recommended number of treatments (three). Only one patient among those who did not observe any improvement received three treatments. Conclusions: Auricular acupuncture is a safe and cheap method to treat hot flushes. It has been effective in numerous and various cases, among which were patients who presented cancer-related menopausal symptoms. It may be applied for a large variety of other symptoms.